Navigating Pastoral Transitions : A Staff Guide - Kerkhoff, Barbara (Book collections on Project MUSE., 2013)
Parish staff members have a unique leadership role when there is a change in pastors. In that transitional time when the current pastor hasn't quite left and the new pastor hasn't quite arrived, they are an anchor that the rest of the parish turns to for guidance. Navigating Pastoral Transitions: A Staff Guide shows, step-by-step, how to navigate this stressful moment in parish life. A detailed Pastor Transition Timeline, as well as solid, field-tested advice, gives readers the tools they need for a smooth transition process. Discover how to use this time of transition to lead the parish to deeper faith and spiritual growth. Help the parishioners and the pastor move together into this new stage of parish life. This book is designed to be used with Navigating Pastoral Transitions: A Parish Leader's Guide and Navigating Pastoral Transitions: A Priest's Guide.